Meows – time to review the trigger threshold?. (16th November 2010) - Dudley, M; Wright, A; Simons, R; McGlennan, A
Abstract : Introduction: The 2003–2005 Confidential Enquiry into Maternal and Child Health (CEMACH) encouraged 'the routine use of a national obstetric early warning chart'. Our trust trialled the CEMACH example of a MEOWS observation chart (Modified Early Obstetric Warning System). Observations exceeding a threshold level fall into colour-coded trigger zones. Two observations in the yellow zone or one in the red zone triggers an obstetric/anaesthetic review. The authors wanted to assess the impact this chart had on the medical workforce with trigger thresholds at the levels suggested by the CEMACH MEOWS. There is little or no validation evident in the literature of MEOWS nor the threshold levels suggested. Modality Red 2 Yellow Temperature High 6 0 Low 0 0 Systolic Blood Pressure High 57 24 Low 10 6 Diastolic Blood Pressure High 38 26 Low 1 2 Heart Rate High 12 18 Low 0 0 Respiratory Rate High 0 2 Low 0 0 Total 125(61.6%) 78(38.4% Method: The authors reviewed 500 charts of 12 h periods of observation in 303 patients. Patients in all areas of the obstetric unit were included. The presence of any trigger in the period was recorded and the observation that triggered, noted. Results: There was a minimum trigger rate of 0.2 triggers/12 h period. 61.6% of triggers were red-zone and 38.4% yellow. Conclusion: Until validation occurs, it is difficult to determine whether this triggering rate is true or due to inappropriate thresholds. This triggering rate requires a frequent response, which has a significant impact on workforce. Further work on sensitivity and specificity of MEOWS is required before questions regarding its benefit can be answered.